Dampak Penilaian Prestasi Kerja Terhadap Motivasi dan Produktivitas Karyawan Outsourcing PT Perdana Perkasa Elastindo - Asrul Siregar; Illah Sailah; M Hasjim Bintoro (Institut Pertanian Bogor, 2006)
The role of consultant services of human resources is to assist people to find the right job in accordance to their skills, and emphasize on the shaping and caring of employees, and improving work productivity through membership in organizations. A worker’s position in a contract is the uncertainty in his work period, which means that if his contract expires, he should be ready to find another job. This causes less seriousness in his work when approaching the termination of his contract, and his motivation and productivity will decrease. It has been found that based on their answers, the average respondents do not understand the functions and objectives of the performance assessment and its result. This indicates a lack of socialization on the company side concerning the execution of assessment. A scale of 0.00 – 0.25 or –0.25 – 0.00 on the Champion scale, categorized as no association, was found when searching for a correlation between the performance assessment and work motivation (to work hard, cooperate, and be responsible). This indicates that there is no clear correlation between those two at PT Perdana Perkasa Elastindo. Some productivities do not have a clear effect on the performance assessment because the respondents have already been required to use all the skills they have at the company. The result of the Rank Spearmen correlation test shown in Table 15 indicates that correlation between the workers’ performance assessment and their maturity ranges between 0.26 and 0.50 or -0.50 and –(0.26), with a correlation of 0.411. This is due to the level of maturity of the workers, who already have understanding and responsibility, and are graduates of tertiary education. Based on the result of this research, the company needs to perform a study concerning the factors influencing the workers’ motivation and productivity periodically, because this research is based only on the condition of the company at this moment, whereas changes can happen any time.